HUBUNGAN ANTARA DISTRIBUSI FITOPLANKTON DENGAN KUALITAS PERAIRAN DI SELAT ALAS, KABUPATEN SUMBAWA, NUSA TENGGARA BARAT - Radiarta, I Nyoman (Bumi Lestari; Vol 13 No 2 (2013), 2013)
Abstract Plankton (phytoplankton and zooplankton) has an essential factor for aquatic ecosystem, because plankton is a primary food source for aquatic animals. This study was carried out in the Alas Strait, Sumbawa Regency on May 2012. Based on the data collected from 32 stations, phytoplankton distributions (abundance and ecology indexes), water quality condition, and relationship between them were examined. Phytoplankton identification results show that a total of 25 species was found, and that species were classified into seven classes. Bacillariophyceae (diatom) was the dominant class found in the study area. Pearson correlation indicated that water temperature, transparency, salinity, nitrate, and phosphate were the parameters significantly affected on phytoplankton distribution and abundance. The results from this study could contribute on the development marine aquaculture in this region in term of pearl aquaculture development.
Keywords: Keywords: Phytoplankton, water quality, marine aquaculture, Alas Strait, Sumbawa